Answer:
SR =3
Step-by-step explanation:
SR + RQ = SQ
2x+23 + x+21 = 14
Combine like terms
3x+44 = 14
Subtract 44 from each side
3x+44-44= 14-44
3x = -30
Divide each side by 3
3x/3 = -30/3
x = -10
SR = 2x+23 = 2(-10)+23 = -20+3 =3
Answer: 3
Step-by-step explanation:
We can start by making an equation.
Since we know the total length of SQ we can add SR + RQ to equal SQ.
The parenthesizes are not necessary but they help for understanding the parts of the equation.
We will remove the parenthesizes and combine like terms.
Now subtract 44 from both sides to cancel it out from the side with x.
Now divide by 3 to isolate x.
So x = -10.
Now we can plug in the value of x into SR.
Solve
So SR = 3
Note: Numbers next to functions are in degrees.
Answer:
Step-by-step explanation:
To simplify the expression, we'll use trigonometric identities.
The identity we'll use is the product-to-sum formula for cosine:
Now, let A = 77 and B = 88
Notice that 77 - 88 = -11 degrees.
Now, we know that cos(-x) = cos(x), so:
Finally, since the cosine function is even (cos(x) = cos(-x)), we have:
Therefore:
See the attachmentfor trigonometric identities formula:
21 phones
210 phones
26 phones
Answer:
21
Step-by-step explanation:
B. 48 sq meters
C. 24 sq meters
D. 7 sq meters
A.
–$70,000
B.
$114,000
C.
$44,000
D.
–$44,000